Literasi Keuangan, Lingkungan Sosial, dan Persepsi Kemudahan Penggunaan sebagai Pendorong Adopsi Pembayaran Digital pada UMKM: Apakah Pendidikan Berperan? - Lestari, Via Okti; Maulida Nurul Innayah (Universitas Muhammadiyah Pontianak, 2026)
Despite the rapid expansion of digital payment services in Indonesia, adoption among MSMEs remains uneven. This study examines the effects of financial literacy, social environment, and perceived ease of use on digital payment adoption and the moderating role of education. Data from 172 MSME owners in Banyumas Regency were analyzed using PLS-SEM. The results indicate that financial literacy, social environment, and perceived ease of use significantly enhance digital payment adoption, while education has no moderating effect. These findings imply that improving financial capability, strengthening business networks, and providing user-friendly digital payment services are more effective than relying on formal educational attainment.